Hahnemann's Sick Proving: A Comprehensive Study on Its Working Methodology - Tiwary, Himanshu Sekhar; Tiwary, Nidhi (Homœopathic Links, 2022)
Background Homoeopathy operates with highly potentised medicines since, during sickness, there is a state of heightened sensitivity to similar stimuli in an individual. The same proposition is also the guiding principle behind one of the advanced methods of Hahnemann, i.e. sick proving. This tool was employed by Hahnemann in his later life to record the symptoms from sensitive and chronic patients. Unfortunately, this collateral method of drug proving has not been examined thoroughly and hence has not been utilised. This study intends to revisit Hahnemann's sick proving and decipher the finer shades of its working methodology.Material and Methods A comprehensive literature search and analysis for sick proving was done from Hahnemann's major works such as Organon of Medicine, the Chronic Diseases, Materia Medica Pura and other literature such as lesser writings, redacted writings, letters, biographies and miscellaneous publications. All the proving records of the Chronic Diseases were examined in terms of their source and methodology and analysed from the perspective of sick proving.Results From the present study, it has distinctly emerged that Hahnemann had a very systemic and methodical process of sick proving observed mainly in unaltering chronic patients. He used to take healthy drug proving symptoms mainly from other sources for his work in the Chronic Diseases and add symptoms from his sick proving as a collateral route. Sick proving was part of follow-up consultation in new as well as extensively proved drugs as evident from the Letter of Hermann Hartlaub in 1834. He added many valuable polychrest drugs in our armamentarium with the help of this method in his book the Chronic Diseases.Conclusion Unlike healthy drug proving, sick proving by Hahnemann has not been thoroughly investigated despite its sound logic and tangible merits. A more detailed study is required to realise the full potential of this wonderful method of drug proving.
Keywords: sick proving; drug proving; chronic diseases; adverse drug reaction (ADR); pharmacovigilance